Emergent Magnetic Fan Structures in Manganite Homojunction Arrays. Issue 35 (29th July 2022) - Guasco, Laura; Khaydukov, Yury; Kim, Gideok; Keller, Thomas; Vorobiev, Alexei; Devishvili, Anton; Wochner, Peter; Christiani, Georg; Logvenov, Gennady; Keimer, Bernhard
Abstract: Devices with tunable magnetic noncollinearity are important components of superconducting electronics and spintronics, but they typically require epitaxial integration of several complex materials. The spin‐polarized neutron reflectometry measurements on La1− x Sr x MnO3 homojunction arrays with modulated Sr concentration reported herein have led to the discovery of magnetic fan structures with highly noncollinear alignment of Mn spins and an emergent periodicity twice as large as the array's unit cell. The neutron data show that these magnetic superstructures can be fully long‐range ordered, despite the gradual modulation of the doping level created by charge transfer and chemical intermixing. The degree of noncollinearity can be effectively adjusted by low magnetic fields. Notwithstanding their chemical and structural simplicity, oxide homojunctions thus show considerable promise as a platform for tunable complex magnetism and as a powerful design element of spintronic devices. Abstract : Manganese oxide homojunctions with gradually modulated doping level host surprisingly complex, long‐range ordered magnetic superstructures whose spin alignment is tunable by low magnetic fields. Homojunctions can thus serve as a powerful design element of all‐oxide spintronic devices.